EFFECT OF ELECTROMAGNETIC FIELD ON THE THERMAL EFFICIENCY OF CONCENTRATED SOLAR COLLECTOR (EXPERIMENTAL STUDY) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2022)
In this work, the effect of electromagnetic field on thermal performance of concentrated parabolic trough solar collector is studied experimentally. A two-axis tracking parabolic trough collector formed of a reflector (mirror tapes matrix), of (2m *1m), and an absorber copper tube (receiver) is designed. Water and water-based magnetic iron oxide (Fe3O4) nanofluid are used as heat transfer fluid in the collector. Three volume concentrations (0.3%, 0.5%, and 0.9%) of nanoparticles are investigated under a magnetic flux of (3.2, 4.3, 6.2, and 7.9*103 Gauss), which is installed at absorber inlet, middle, and exit. The three coils are connected to a DC-generator to control the electromagnetic field. The electromagnetic field effect on water flow in the absorber is found weak. A significant thermal improvement is figured when utilizing ferrofluid as a heat transfer fluid in the absorber. It is represented by higher temperature distributions in the absorber and higher solar collector efficiency compared with base fluid.